Analisis Rasio Keuangan Terhadap Return Saham Pada Perusahaan Manufaktur Yang Go Public Di BEI Periode 2009-2013 - Raharjo, Setyawan, Drs. Ma'ruf, M.M (2015)
The research to prove whether the financial ratios as measured by the variable Current Ratio (CR), Return on Equity (ROE), and Earning per Share (EPS) significantly together to return stock at manufkatur company. And to know among these variables, which significantly on stock return manufkatur go public on the Stock Exchange Indonesia 2009-2013. Data analysis methods used by multiple linear regression analysis. Sample acquired 52 companies manufacturing go public in Indonesia Stock Exchange 2009-2013 period. Analysis of the results of the regression performed after classical assumption test. Based on the survey results revealed that the Current Ratio (CR), Return on Equity (ROE) and Earning per Share (EPS), only the variable Current Ratio (CR) and Return on Equity (ROE) were shown to have a significant effect on stock returns. Current Ratio (CR) is the most variable The dominant on stock returns Keywords: CR, ROE, EPS, Stock Return